2024
DOI: 10.2174/1386207326666230331075912
|View full text |Cite|
|
Sign up to set email alerts
|

WITHDRAWN: Identification and Validation of Autophagy-related Genes in Sepsis-related Acute Kidney Injury (S-AKI) via Bioinformatics Analysis

Abstract: Background: Acute kidney injury is one of the most common complications of sepsis, while autophagy has been reported to exert protective effects against kidney diseases. background: Acute kidney injury is one of the most common complications of sepsis. Autophagy has been reported to make protective effects in kidney diseases, therefore in this study, we identified the key autophagy genes in sepsis-related acute kidney injury(S-AKI) through bioinformatics analysis of sequencing data, and activated autophagy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Two additional studies published recently also indicated that MAP1LC3B may influence the development of sepsis and sepsis-related acute kidney injury. [36,37] Therefore, based on previous reports and the results of our study, we hypothesize that MAP1LC3B might have an important role in stimulating immune infiltration in blood tissues and thus contributes to the progression of septic shock. Currently, the specific relationships between MAP1LC3B and septic shock have not been revealed; thus, our findings provide reliable evidence for the correlation between the 2 and validate the fundamental roles of MAP1LC3B in septic shock-related immune infiltration.…”
Section: Discussionsupporting
confidence: 61%
“…Two additional studies published recently also indicated that MAP1LC3B may influence the development of sepsis and sepsis-related acute kidney injury. [36,37] Therefore, based on previous reports and the results of our study, we hypothesize that MAP1LC3B might have an important role in stimulating immune infiltration in blood tissues and thus contributes to the progression of septic shock. Currently, the specific relationships between MAP1LC3B and septic shock have not been revealed; thus, our findings provide reliable evidence for the correlation between the 2 and validate the fundamental roles of MAP1LC3B in septic shock-related immune infiltration.…”
Section: Discussionsupporting
confidence: 61%